(untitled) (Stato, Chiese e pluralismo confessionale, 2011)
SOMMARIO: 1. Premessa – 2. L’ente religioso imprenditore – 3. Rinnovata centralità di “frate sole” nel III millennio: le parrocchie e il fotovoltaico – 4. Il Magistero della Chiesa cattolica in tema di salvaguardia dell’ambiente – 5. Considerazioni conclusive. ABSTRACT: The establishment of a social enterprise for the production and sale of electricity through the creation of a photovoltaic system by imposing some parishes of Mantua shows that there is no conflict between the specific nature of ecclesiastical entity and the exercise by this socially useful economic activity, because the economic activity in order to provide the capital resources required to achieve the purpose of religion or belief, does not change the nature of ecclesiastical entity, because it does not absorb or blur the religious or of worship but rather reinforces the essence, as related and instrumental to this The invitation to promote renewable energy to protect the environment, has been the subject of interventions at various levels by both the Italian state and by the European Community, also Magisterium of the Catholic Church has often called for a real ecological conversion and an ecumenical commitment to that effect Associated Parishes are an example of civil economy, characterized by human sociality and reciprocity, as opposed to a utilitarian vision of the market based on the logic of exchange of equivalents.